Keabsahan Hukum Pernikahan Tanpa Adanya Walimatul Ursy di Masa Kahar Pandemi Covid-19 - Yapiter Marpi (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2021)
ABSTRACT This study aims to find out and discuss about the perspective of marriage reception is a food banquet in order to experience the same happiness as other receptions, it's just that he is sunnah and more important. One of the wisdoms of wedding receptions is to inform or advertise and publicize weddings. Regardless fuqaha disputes related opinions that are responsible for financing, whether charged to the bridegroom or the bride's bride's family. The government through the Ministry of Religion has issued a Circular Minister of Religion Number SE. 15 of 2020 concerning Guidelines for Organizing Religious Activities in Worship Houses in Realizing COVID Productive and Safe Communities in the Pandemic Period. Is a large-scale pembatasa for all activities including the wedding reception procession that can no longer be held in the crowded public. The reality has happened to people who want to have marriages are restricted and can no longer gather more than 5 people or more. Covid-19's time was not an obstacle to connecting friendship between the bride and groom's wedding which was held in a special way Walimatul Ursy during the Covid-19 pandemic. The problem highlighted in the community whether it would be legal if it was not published publicly as usual normally if the marriage ceremony had been held without a reception or Walimatul Ursy. Keywords; Marriage law, Walimatul Ursy, period of force majeure.